Numerical analysis of surface integrity in parallel turning Part A: Influence of cutting tool nose radius. (2021) - Kanakaraju, Veldi; Hassan, Faisal; Rathinam, Kalidasan
Abstract: Nose radius of a cutting tool is an important factor in finding the surface integrity of turned parts. The current research work deals with numerical analysis of surface residual stress generated during parallel turning using finite element method based software. Appropriate material model was used for parting the chip from work material. Nose radius is a vital process variable especially in parallel turning. The main motive of the current research work is to estimate the influence of nose radius on axial and circumferential residual stresses retained by machined work surfaces. The results revealed that with the increment in cutting tool nose radius, the residual stress of compressive nature along cutting and feed direction increases for the machined surface of front and rear tool. For all the nose radii, residual stresses raised with the rise in cutting speed. For nose radius of 0.5 mm and 250 m/min cutting speed with feed 0.2 mm/rev, the highest compressive circumferential and axial stress of the surface turned by second tool is 1696 MPa and 1838 MPa respectively. Higher nose radius causes larger dead metal and stagnation zone which in turn causes higher surface residual stresses.